Vacuum-assisted thermal drying of wastewater treatment sludge - Avsar, Yasar; Saral, Arslan; Ilhan, Fatih; Akyuz, Bahar; Gonullu, Mustafa Talha (TAYLOR & FRANCIS INC, 2021)
Sludge drying is one of the main problems of wastewater treatment plants. It is very important to facilitate the drying process in terms of drying efficiency, time duration, and cost of the processes, so that transportation and dumping of sludge will accordingly be realized effectively. In this study, vacuum assisted thermal drying was studied. Under vacuum conditions, the water content of the sludge was examined easier than at atmospheric pressure in the drying process. For this reason, in this study, time, temperature, and sludge mass surface area on drying efficiency were evaluated under two different pressure levels, such as 30 mbar and 1,000 mbar. To optimize these parameters, the Response Surface Methodology approach was utilized. Results showed that the effect of vacuum condition on sludge drying was remarkable at obtaining at least 65% of solid material ratio in sludge, which is the lowest limit value on landfilling legislation in Turkey. Data obtained from the study shows that, especially at high temperatures, contribution on sludge drying of vacuum condition is more effective in terms of drying time. A smaller sludge surface area is also found more significant on vacuum drying. Implications: Drying the sludge under low pressure shortens the drying time. It is possible to reach higher solid material ratio under low pressure. Time, temperature, and surface areas of sludge are effective parameters in vacuum drying.
Keywords: Engineering; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences